A review of observational instruments to assess the motivational environment in sport and physical education settings. Issue 1 (1st January 2016) - Smith, Nathan; Quested, Eleanor; Appleton, Paul R.; Duda, Joan L.
ABSTRACT: To date, the majority of research grounded in achievement goal frameworks (AGT) and self-determination theory (SDT), which has examined the coach-created motivational environment and its correlates, has relied exclusively on athletes' self-reported perceptions. This limits progress in the field as objective data on real-life events could be used to further identify what coaches and teachers do and say to 'motivate' their athletes and students to influence their skill development, performance and well-being. Such information may help inform how coaches and teachers should be trained to create more motivationally adaptive environments and could help extend results derived from self-report measures. This review outlines the observational systems that are currently available and the research related to AGT and/or SDT-based objective assessments of motivational dimensions of the coaching and physical education (PE) environment. Future research could utilise information in this review to employ and/or amend one of the available observation systems to address important questions related to the observed motivational environment in sport and PE.